Pengaruh model blended learning terhadap motivasi dan prestasi belajar siswa SMK - Izuddin Syarif (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2012)
Penelitian ini bertujuan untuk mengetahui perbedaan motivasi dan prestasi belajar siswa dalam mata pelajaran KKPI antara siswa yang menggunakan model face-to-face learning dan siswa yang menggunakan model blended learning, peningkatan motivasi dan prestasi belajar siswa dalam mata pelajaran KKPI akibat penerapan model blended learning, dan interaksi pengaruh penerapan model pembelajaran dan motivasi terhadap prestasi belajar KKPI siswa SMKN 1 Paringin. Penelitian kuasi eksperimen ini menggunakan dua kelompok, yaitu kelompok eksperimen yang menggunakan model blended learning dan kelompok kontrol yang menggunakan model face-to-face learning. Populasi penelitian adalah siswa kelas XI SMKN 1 Paringin. Sampel penelitian berjumlah 57 siswa terbagi atas 30 siswa kelompok kontrol dan 27 siswa kelompok eksperimen. Pengumpulan data menggunakan kuesioner dan tes soal pilihan ganda. Hasil penelitian menunjukkan ada perbedaan yang signifikan antara motivasi dan prestasi belajar siswa yang menggunakan model blended learning dan siswa yang menggunakan model face-to-face learning, ada peningkatan motivasi dan prestasi belajar siswa yang signifikan akibat penerapan model blended learning, dan tidak terdapat interaksi pengaruh penerapan model pembelajaran dan motivasi terhadap prestasi belajar siswa. THE INFLUENCE OF BLENDED LEARNING MODEL ON MOTIVATION AND ACHIEVEMENT OF VOCATIONAL SCHOOL STUDENTAbstractThe objective of the study is to reveal the differences of the learning motivation and achievement of the students using face-to-face learning model compared to those using blended learning model, the improvement of students' learning motivation and achievement due to the use of blended learning model, and the interaction of the effect of learning model and motivation on students' learning achievement in KKPI lesson. This quasi-experimental study used two groups: the experimental group who were taught using blended learning and control group who were taught using face-to-face learning. The population was 11th grade students of SMKN 1 Paringin. A sample of 57 students was divided into 2 groups, with 30 students as the control group and 27 students as the experimental group. The techniques for collecting the data were a test method by giving a written test and non-testing method by distributing a questionnaire. The results of study show that there is significant difference between the learning motivation and achievement of the students using face-to-face learning compared to those using blended learning model, there is a significant increase in learning motivation and achievement due to the use of blended learning model, and there is no interaction of the effect of learning model and motivation on students' learning achievement in KKPI lesson.